MODELLING AND TESTING OF SYNCHRONOUS MOTORS WITH PERMANENT MAGNETS - HORIASHCHENKO, KOSTYANTYN; STETSIUK, VIKTOR; HORIASHCHENKO, SERHIY; LYSYI, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Permanent magnet synchronous motors (PMSM) have been known for a long time. In Ukraine, this type of motors is not used widely enough. Synchronous motors require less energy to provide sufficient performance than the well-known induction motor. It shows what PMSM require control equipment to ensure smooth rotor start, motion and stop. Three schemes like Volt-Frequency (VF), Sensorless Vector Control (SVC) and Vector Control (VC) to control motors are currently known. But only the control of the encoder at VC control type ensures an adequate start of the synchronous motor. PMSM allow you to archive a constant increase in speed, a quick response to the rotor load. The output torque of the PMSM is automatically regulated by the supply voltage and current with stable rotations. The article shows results of comparing existing PMSM motor with an encoder with use of Vector Control Driver and virtual model of PMSM with a variable load. In the mathematical model of a synchronous motor, the equation of the stator of an asynchronous motor is used, which takes into account the interaction with the rotor through the magnetic flux. The position of the rotor magnets is determined by the rotor design itself, regardless of the stator voltages and currents. The instantaneous value of the induced electromotive force (EMF) is also determined, which makes it possible to determine the stator currents and the rotor torque. Permanent Magnet Synchronous Motors (PMSMs) are widely used in machinery such as elevators, shredders, and conveyors due to their ability to "hold position" when the motor brakes are off, with the load supported solely by the PMSM motor itself. The high-speed response of the frequency converter together with the control system ensures a constant rate of increase in the motor speed regardless of load changes. Thus, the synchronous motor maintains stable mechanical characteristics regardless of changes in load and rotation frequency. At the same time, the motor voltage and current are dynamically adjusted to ensure the desired output performance